Risk factors, clinical features, and outcomes of premature acute myocardial infarction - Liu, Qi; Shi, Rui-Juan; Zhang, Yi-Man; Cheng, Yi-Heng; Yang, Bo-Sen; Zhang, Yi-Ke; Huang, Bao-Tao; Chen, Mao (Frontiers in Cardiovascular Medicine, 2022)
Aims To investigate the risk factors, clinical features, and prognostic factors of patients with premature acute myocardial infarction (AMI). Materials and methods A retrospective cohort study of patients with AMI included in data from the West China Hospital of Sichuan University from 2011 to 2019 was divided into premature AMI (aged < 55 years in men and < 65 years in women) and non-premature AMI. Patients’ demographics, laboratory tests, Electrocardiography (ECG), cardiac ultrasound, and coronary angiography reports were collected. All-cause death after incident premature MI was enumerated as the primary endpoint. Results Among all 8,942 AMI cases, 2,513 were premature AMI (79.8% men). Compared to the non-premature AMI group, risk factors such as smoking, dyslipidemia, overweight, obesity, and a family history of coronary heart disease (CHD) were more prevalent in the premature AMI group. The cumulative survival rate of patients in the premature AMI group was significantly better than the non-premature AMI group during a mean follow-up of 4.6 years (HR = 0.27, 95% CI 0.22–0.32, p < 0.001). Low left ventricular ejection fraction (LVEF) (Adjusted HR 3.00, 95% CI 1.85–4.88, P < 0.001), peak N-terminal pro-B-type natriuretic peptide (NT-proBNP) level (Adjusted HR 1.34, 95% CI 1.18–1.52, P < 0.001) and the occurrence of in-hospital major adverse cardiovascular and cerebrovascular events (MACCEs) (Adjusted HR 2.36, 95% CI 1.45–3.85, P = 0.001) were predictors of poor prognosis in premature AMI patients. Conclusion AMI in young patients is associated with unhealthy lifestyles such as smoking, dyslipidemia, and obesity. Low LVEF, elevated NT-proBNP peak level, and the occurrence of in-hospital MACCEs were predictors of poor prognosis in premature AMI patients.